STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK DI SDN 2 LAMUK, KECAMATAN KALIWIRO, KABUPATEN WONOSOBO - Maelani, Dwiki; Asy’ari, Abdurrohman; Al-Halim, A. Adibudin (Pendidikan Agama Islam (S2), UNSIQ Wonosobo, Jawa Tengah, 2025)
The strategies implemented by Islamic religious education teachers in the learning process, particularly in developing students' morals, have not met our expectations. Therefore, this study will focus on examining Islamic religious education teachers' strategies in developing students' morals at SDN 2 Lamuk. The study aims to answer the research questions by utilizing qualitative methods, including interviews, observation, and documentation, for data collection. At SDN 2 Lamuk, Islamic Religious Education teachers implement various strategies to foster students' morals. These strategies include leading by example, providing guidance, instilling habits, sharing stories from the Quran and the life of the Prophet Muhammad (peace be upon him), utilizing real-life examples, conducting lectures, and facilitating discussions. Furthermore, student moral development at SDN 2 Lamuk includes religious guidance activities, implementing disciplinary measures, fostering cooperation between teachers to enhance moral development, and enhancing cooperation between teachers and parents. At SDN 2 Lamuk, students' moral development is facilitated through the implementation of Islamic Religious Education (PAI) teacher strategies. These strategies serve various purposes, including motivating students, helping them achieve their goals, and guiding teaching and learning activities. Furthermore, these strategies play a crucial role in fostering students' moral development. Carrying out various strategic roles in daily life can effectively cultivate noble morals among students. By actively participating in religious activities at school, students can strive to achieve their desired goal of developing morals and virtuous character. This active involvement serves to increase student enthusiasm and foster a sense of purpose.